Associational pluralism – is it possible to build on this conceptual heritage? - Lukšič, Andrej (Teorija in praksa, 2024)
The article reflects on a key category introduced by Adolf Bibič in his 1990 theoretical work Civil Society and Political Pluralism; namely, association pluralism. Bibič introduced this concept into Slovenian political thought to grasp the diverse social and political developments of the 1980s and to open up a new view of political pluralism that moves beyond party pluralism. The author therefore asks whether the notion of associational pluralism still holds sufficient explanatory potential and is worth preserving and developing further, or whether it can be used to deal with a new social and political reality, i.e., political pluralism, which is also strongly marked by multifaceted environmental issues
Keywords: asociacijski pluralizem; associational pluralism; civil society; civilna družba; država; party pluralism; political pluralism; Politične vede; politični pluralizem; state; strankarski pluralizem